2018
DOI: 10.1016/j.ijsu.2018.03.072
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for cervical gastro-oesophageal anastomosis during minimally invasive oesophagectomy

Abstract: Jiang's anastomosis technique remarkably reduces the incidence of gastro-oesophageal anastomotic leakage, stricture and reflux, and it is a safe and effective technique for minimally invasive oesophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…1 ). Details of these studies 15–18,32–67 are shown in Table 1 . The majority of included studies reported on open oesophagectomy.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Details of these studies 15–18,32–67 are shown in Table 1 . The majority of included studies reported on open oesophagectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Once it occurs, patients suffered decreased quality of life, protracted hospitalization or even death. This is why there were many innovations and modifications in reconstructive surgery including functional end-to-end stapling, triangulating stapling, T-shaped linear stapling, pre-embedded stapling, and so forth (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Although efficacy of mechanical anastomosis had been reported previously ( 12 , 16 , 17 ), much effort had still been tried to better off the clinical outcome and simplify the procedure ( 18 , 19 ). Chen et al ( 20 ) reported that use of pleural flaps in the upper mediastinum would reduce the incidence of cervical subcutaneous emphysema and anastomotic leakage into pleural cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of causes and preventive measures of postoperative complications, especially anastomotic leakage, some scholars have made many attempts to find the answer. [8][9][10][11] Previous studies showed that delayed gastric emptying (gastric-tube bloating) after esophagectomy was related to the occurrence of anastomotic leakage and gastric perforation, and the possible reason was that gastric-tube dilatation and the gravitational effect on the stomach without pleural fixation increased the tension on the anastomosis. [12][13][14] Asteriou et al 15 reported that suturing the mobilized pleura over the completed anastomosis could reduce anastomotic leakage after Ivor-Lewis esophagogastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In the concept of ERAS system, reducing postoperative complications is an important task. In terms of causes and preventive measures of postoperative complications, especially anastomotic leakage, some scholars have made many attempts to find the answer 8–11 . Previous studies showed that delayed gastric emptying (gastric‐tube bloating) after esophagectomy was related to the occurrence of anastomotic leakage and gastric perforation, and the possible reason was that gastric‐tube dilatation and the gravitational effect on the stomach without pleural fixation increased the tension on the anastomosis 12–14 .…”
Section: Introductionmentioning
confidence: 99%